Neutralizing Anti-Cytokine Autoantibodies Against Interferon-α in Immunodysregulation Polyendocrinopathy Enteropathy X-Linked - Rosenberg, Jacob M.; Maccari, Maria E.; Barzaghi, Federica; Allenspach, Eric J.; Pignata, Claudio; Weber, Giovanna; Torgerson, Troy R.; Utz, Paul J.; Bacchetta, Rosa (Frontiers in Immunology, 2018)
Anti-cytokine autoantibodies (ACAAs) have been described in a growing number of primary immunodeficiencies with autoimmune features including Autoimmune Polyendocrine Syndrome Type I (APS-1), a prototypical disease of defective T cell central tolerance. Whether defects in peripheral tolerance lead to similar ACAAs is unknown. Immunodysregulation Polyendocrinopathy Enteropathy X-linked (IPEX) is caused by mutations in FOXP3, a master regulator of T regulatory cells (Treg), and consequently results in defective T cell peripheral tolerance. Unique autoantibodies have previously been described in IPEX. To test the hypothesis that ACAAs are present in IPEX, we designed and fabricated antigen microarrays. We discovered elevated levels of IgG ACAAs against interferon-alpha (IFN-alpha) in a cohort of IPEX patients. Serum from IPEX patients blocked IFN-alpha signaling in vitro, and blocking activity was tightly correlated with ACAA titer. To show that blocking activity was mediated by IgG and not other serum factors, we purified IgG and showed that blocking activity was contained entirely in the immunoglobulin fraction. We also screened for ACAAs against IFN-alpha in a second geographically distinct cohort. In these samples, ACAAs against IFN-alpha were elevated in a post-hoc analysis. In summary, we report the discovery of ACAAs against IFN-alpha in IPEX, an experiment of nature demonstrating the important role of peripheral T cell tolerance in preventing the development of IFN-alpha ACAAs.